2023
DOI: 10.3390/fermentation9060551
|View full text |Cite
|
Sign up to set email alerts
|

Moisture-Induced Effects on Lignocellulosic and Humification Fractions in Aerobically Composted Straw and Manure

Abstract: Humic substances affect compost stability and maturation. However, the intricate structure of lignocellulosic materials hinders the biodegradation of cellulose, hemicellulose, and lignin, often promoting the use of synthetic additives which results in microbial inactivation and death. Therefore, this study examined the effects of optimal moisture levels (MC1 = 45%, MC2 = 55%, and MC3 = 65%) on lignocellulosic and humification fractions in aerobically composted straw and manure. The study showed that 65% moistu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…At the end of composting, the hemicellulose content of PM, CD, SM, and CM decreased by 12.35, 8.51, 7.46, and 3.38%, respectively, and the degradation of hemicellulose in PM was significantly higher than other composts ( p < 0.05), while the ratio of hemicellulose in dry matter of DM increased by 2.46% ( Figure 2D ). Ghanney et al (2023) found that when the initial content of hemicellulose in the compost was higher than that of cellulose, hemicellulose was more likely to be degraded than cellulose and lignin. The above results showed that the degradation of cellulose in composting from cow manure and sheep manure was obvious and the degradation of hemicellulose in composting from pig manure and chicken manure was prominent, indicating that the degradation of organic components might be related to its initial content.…”
Section: Resultsmentioning
confidence: 99%
“…At the end of composting, the hemicellulose content of PM, CD, SM, and CM decreased by 12.35, 8.51, 7.46, and 3.38%, respectively, and the degradation of hemicellulose in PM was significantly higher than other composts ( p < 0.05), while the ratio of hemicellulose in dry matter of DM increased by 2.46% ( Figure 2D ). Ghanney et al (2023) found that when the initial content of hemicellulose in the compost was higher than that of cellulose, hemicellulose was more likely to be degraded than cellulose and lignin. The above results showed that the degradation of cellulose in composting from cow manure and sheep manure was obvious and the degradation of hemicellulose in composting from pig manure and chicken manure was prominent, indicating that the degradation of organic components might be related to its initial content.…”
Section: Resultsmentioning
confidence: 99%
“…Compost’s maturity and stability are connected to its quality. While maturity refers to a product’s ability to be utilized effectively in agriculture and is related to features of phytotoxicity and plant growth, stability relates to a product’s organic matter’s resistance to extensive degradation or higher microbiological activity [ 13 ]. In order to obtain high-quality compost, it is necessary to optimize composting process conditions [ 14 ].…”
Section: Introductionmentioning
confidence: 99%